ANALISIS KEPERCAYAAN DIRI ATLET BOLA TANGAN PUTRI KABUPATEN PURWOREJO MENJELANG PERTANDINGAN - Nurlita Putri Ismiati, Sherly; Pramono, Harry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the phenomenon of declining performance among female handball athletes in Purworejo Regency during official matches due to nervousness and a lack of self-confidence, even though they demonstrated good technical skills during practice. The purpose of this study was to conduct an in-depth analysis of the athletes’ self-confidence levels prior to matches. Using a descriptive qualitative approach, data were collected through semi-structured interviews, observations, and documentation of athletes, coaches, and administrators. The results of the study indicate that athletes’ self-confidence levels are uneven and still fluctuate, influenced by six main components: self-belief, anxiety control, optimism, competition experience, support system, and mental readiness. Competition experience was found to be the most dominant factor in shaping athletes’ readiness. Mental readiness is generally not yet optimal due to the absence of structured mental training programs integrated into routine training schemes. This study concludes that athletes’ self-belief is the result of a complex dynamic interaction between emotional regulation, social support, and experience. Therefore, a structured mental strenghthening program is needed to help athletes consistenly achieve peak performance.